Non-Invasive Blood Pressure Monitoring Using a Single-Channel PPG Sensor With Adaptive Kalman Algorithm and 4-LED Arrayed Structure - Shi, Wei; Dong, Linxi; Cheng, Jiagen; Mu, Yuanbin; Yue, Chenxi; Hu, Mengyi; Zhong, Yuxin; Gao, Yu; Liu, Chaoran; Wang, Xiaoyuan; Yu, Jing; Yao, Defei; et al. (IEEE transactions on instrumentation and measurement, 2024)
Recently, the pulse wave transit time (PTT) method for Non-Invasive blood pressure (NIBP) monitoring based on single-channel photoplethysmography (PPG) signal has attracted much attention due to its advantages of simple operation, low cost, and high accuracy. However, traditional measurement equipment still faces problems such as detection results being easily affected by noise and low comfort. Accordingly, this article proposes a flexible and wearable heart rate (HR) and blood pressure (BP) monitoring sensor based on single-channel PPG. A novel 4-LED arrayed optoelectronic structure is designed, a data acquisition system based on LabVIEW is built, physiological signal preprocessing and feature point extraction algorithms are studied to reduce the noise of motion artifacts (MAs), and four BP regression models are established to improve measurement accuracy. Based on the PDMS substrate and the double-layer serpentine electrode structure, the sensor is endowed with the ability to fit perfectly with the skin and maintain co-conformity. The comparison with the standard values measured by Omron shows that the mean relative error rate of HR is 1.9%, and the mean error (ME) and mean absolute error (MAE) ± standard deviation (STD) of systolic BP (SBP) and diastolic BP (DBP) are as low as −0.08 and 2.64~± ~2.34 mmHg and 0.14 and 2.87~± ~2.69 mmHg, respectively. The results are less than the standards set by the American Association for the Advancement of Medical Instrumentation (AAMI) for measuring the accuracy of BP monitors and reaching the level of Grade A of the British Hypertension Society (BHS).